The Analysis of Food Symbols in the ‘Pakan’ Ritual of the Penan Saoh in Ulu Jelalong Community, Bintulu Sarawak - Keti, Sarina anak; Magiman, Mohamad Maulana; Yusof, Haji Ahmad bin Mohd.; Abdullah, Azlina binti; Bakar, Fauziah Abu (International Journal of Membrane Science and Technology, 2023)
The Pakan ritual is a performance performed in the Penan Saoh Ulu Jelalong community to be presented to Baleik. The presentation consists of symbolic elements based on each type of food served. These symbolic elements are involved with the belief and cosmological system that surround the lives of Penan Saoh community. The main focus of this research is to analyse the symbol of food in the Pakan ritual from the viewpoint of non-verbal communication. This research used an ethnographic approach, and the researchers also participated in the ritual. The data was collected through an in-depth interview with the main informant, Vaie Jau’u, and other ritual practitioners. The research was conducted in Kampung Julaihi Penan Saoh Ulu Jelalong, Bintulu, Sarawak. The data analysis found that the food delivered to Baleik had its own meaning and could be interpreted through shape, colour, and the way it was presented. The food in the Pakan tray means love, gratitude, prayer, and hope for more sustenance in the upcoming year. The research also found that the ritual is still practiced to this day by the Penan Saoh Ulu Jelalong community and becomes the identity of its existence in the state of Sarawak.